2012
DOI: 10.3892/or.2012.1862
|View full text |Cite
|
Sign up to set email alerts
|

Department of ENT, Nanfang Hospital, Southern Medical University, Guangzhou 510515, P.R. China

Abstract: Abstract. Mitogen-activated protein kinase phosphatase 5 (MKP-5)/DUSP10 acts as a phosphatase of stress-activated kinases (JNK and p38), but its activity towards ERK has not been demonstrated. In the present study we observed that MKP-5 interacts with ERK, retains it in the cytoplasm, suppresses its activation and downregulates ERK-dependent transcription. These data suggested a novel MKP-5 function as a scaffold protein for the ERK pathway. We analyzed MKP-5 gene expression in several tumors, and found that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…We explored the possibility that mir-17~92 increases ERK activation via suppression of dual-specificity phosphatases (DUSPs), which are well-known regulators of numerous MAPK family proteins, including ERK [57]. In particular, DUSP2, DUSP7 and DUSP10 suppress ERK activity and are demonstrated or predicted targets of mir-17~92 miRNAs [48, 5860]. Interestingly, a recent publication linked miR-92 and DUSP10 to PDAC cell proliferation in vitro , suggesting that there may indeed be an important role for this regulatory axis in pancreatic tumorigenesis [61].…”
Section: Discussionmentioning
confidence: 99%
“…We explored the possibility that mir-17~92 increases ERK activation via suppression of dual-specificity phosphatases (DUSPs), which are well-known regulators of numerous MAPK family proteins, including ERK [57]. In particular, DUSP2, DUSP7 and DUSP10 suppress ERK activity and are demonstrated or predicted targets of mir-17~92 miRNAs [48, 5860]. Interestingly, a recent publication linked miR-92 and DUSP10 to PDAC cell proliferation in vitro , suggesting that there may indeed be an important role for this regulatory axis in pancreatic tumorigenesis [61].…”
Section: Discussionmentioning
confidence: 99%
“…Dusp6 and Dusp10 acts as negative feedback regulators of ERK signalling [24,31]. Conversely, genes such as receptor tyrosine kinase KIT, its ligand stem cell factor (SCF) and KRAS, which induce ERK phosphorylation and promote cell proliferation [32], were upregulated by ascites.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that expression of DUSP3 and DUSP10 was upregulated in AML. DUSP10 was reported to be up-regulated in colorectal cancer and kept Erk in cytosol by direct interaction, suggesting that DUSP10 also act as adaptor protein [21].…”
Section: Discussionmentioning
confidence: 99%